Perceptions of smallholder vegetable farmers and extension officers regarding the extension service in the Hhohho region Swaziland - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2018.